Understanding Human–Canid Conflict and Coexistence: Socioeconomic Correlates Underlying Local Attitude and Support Toward the Endangered Dhole (Cuon alpinus) in Bhutan - Thinley, Phuntsho; Rajaratnam, Rajanathan; Norbu, Lam; Dorji, Lungten; Tenzin, Jigme; Namgyal, Chhimi; Yangzom, Choney; Wangchuk, Tashi; Wangdi, Sonam; Dendup, Tshering; Tashi, Sonam; Wangmo, Cheten (Frontiers in Conservation Science, 2021)
Understanding human-canid conflict and coexistence must focus on documenting human-canid interactions and identifying underlying drivers of reciprocal human attitude which enables appropriate strategies to minimize conflict and forge coexistence. The dhole (Cuon alpinus), Asia’s most widely distributed wild canid, is highly threatened from human persecution and anthropogenic activities. Despite its ‘Endangered’ status, ecological role as an apex predator, and negative interactions with humans, dhole-specific attitude studies are limited, thus hindering the development of a comprehensive dhole conservation strategy. Here, we investigate the influence of socio-economic factors of age, gender, income, residency inside/outside a protected area (PA), and other variables (cultural beliefs, livestock loss, and quantity of livestock loss) on local people’s attitudes and support for dhole conservation in the Himalayan Kingdom of Bhutan. We conducted a semi-structured questionnaire survey of 1,444 households located within PA and non-PA from four representative regions in the country. Using R programming, we ran a Pearson’s chi-square test of independence to test overall difference in attitude and support for dhole conservation, followed by recursive partitioning through a conditional inference regression tree to identify their significant covariates with the highest explanatory power. Majority (79.1%) of respondents (χ^2 = 488.6; df = 1; p < 0.001) disliked the dhole over those who liked it. More than half (57.7%) (χ^2 = 412.7; df = 2; p < 0.001) opposed dhole conservation over those who either supported or remained neutral. Experience of livestock loss to dholes was the primary (p < 0.001) factor influencing negative attitude and opposition to dhole conservation, despite an acknowledgement of the dhole’s ecological role in controlling agricultural crop predators. Our study, which is the first-ever survey in Bhutan solely focused on investigating human attitudes and perceptions toward the dhole, indicates that livestock loss to dholes transcends all positive attitudes to the species and drives a predominant dislike and opposition to its conservation. To improve attitude and support toward the dhole and to foster dhole-human coexistence, livestock predation by dholes needs alleviation by improving existing animal husbandry, in conjunction with promoting conservation awareness on this species.